Nitrogen use efficiency in cotton: Challenges and opportunities against environmental constraints - Shah, Adnan Noor; Javed, Talha; Singhal, Rajesh Kumar; Shabbir, Rubab; Wang, Depeng; Hussain, Sadam; Anuragi, Hirdayesh; Jinger, Dinesh; Pandey, Himanshu; Abdelsalam, Nader R.; Ghareeb, Rehab Y.; Jaremko, Mariusz (Frontiers in Plant Science, 2022)
Nitrogen is a vital nutrient for agricultural, and a defieciency of it causes stagnate cotton growth and yield penalty. Farmers rely heavily on N over-application to boost cotton output, which can result in decreased lint yield, quality, and N use efficiency (NUE). Therefore, improving NUE in cotton is most crucial for reducing environmental nitrate pollution and increasing farm profitability. Well-defined management practices, such as the type of sources, N-rate, application time, application method, crop growth stages, and genotypes, have a notable impact on NUE. Different N formulations, such as slow and controlled released fertilizers, have been shown to improve N uptake and, NUE. Increasing N rates are said to boost cotton yield, although high rates may potentially impair the yield depending on the soil and environmental conditions. This study comprehensively reviews various factors including agronomic and environmental constraints that influence N uptake, transport, accumulation, and ultimately NUE in cotton. Furthermore, we explore several agronomic and molecular approaches to enhance efficiency for better N uptake and utilization in cotton. Finally, this objective of this review to highlight a comprehensive view on enhancement of NUE in cotton and could be useful for understanding the physiological, biochemical and molecular mechanism of N in cotton.